Role of wind stress directional steadiness in modulating mesoscale air-sea interactions in the Western Arabian Sea - Xingyu Liu; Sana Ben Ismail; Yuntao Wang (Frontiers in Marine Science)
Mesoscale air-sea interactions reveal the dependence between wind stress and sea surface temperature (SST) where the wind stress directional steadiness (WSDS) serves as a critical role in modulating such interaction. Using satellite-derived SST and reanalysis wind stress data (2003–2022), this study investigates WSDS-mediated coupling in the western Arabian Sea, demonstrating that during the summer monsoon, persistently high WSDS creates optimal conditions for air-sea interactions. The coupling coefficients between wind stress curl (WSC) and crosswind SST gradient (CWSG) exhibits a monotonic strengthening from May (r = 0.80) to September (r = 0.93), with prolonged high WSDS enhancing coupling coefficients through cumulative effects. This intense coupling arises from southwest monsoon-driven coastal upwelling that generates sharp SST fronts. In contrast, the winter monsoon lacks upwelling and frontal activity, suppressing the interactions. Transitional seasons exhibit intermediate behavior that spring shows strengthening coupling as WSDS increases with monsoon onset, while autumn exhibits diminishing coupling as WSDS declines post-monsoon. These results highlight WSDS as a key regulator of mesoscale air-sea interactions in monsoon-dominated regions.